ANALISIS FINANSIAL ALAT PENGUKUS BAGLOG JAMUR TIRAM (Pleurotus ostreatus) TIPE RAK - Meiman Slamet Hawan; Endo Argo Kuncoro; Hary Agus Wibowo (Universitas Sriwijaya, 2012)
The research objective was to analyse the financial aspect of the steamer rack type of oyster mushroom (Pleurotus ostreatus) baglog. The research was conducted from September 2011 to May 2012 at Kumbung jamur tiram, Talang Buruk Palembang. The methods used in this research were financial analysis that includes cost, the investment (NPV, Net B/C and BEP) and sensitivity analysis. The results showed that the average total cost per year was Rp. 20,724,527.00. The production plan was based on an assumption that 100% from selling price of oyster mushrooms Rp. 15.000,00 for one year was Rp. 26,775,000.00. NPV value was Rp. 11,875,188.00 representing the benefits value over the business life of 3 years. The B/C ratio calculation was 1.25. Break-even point (BEP) was on the price of Rp. 15.000 per kg or 1.381,63 kg of production volume. The results of sensitivity analysis of NPV values was obtained when 10% increase in production costs was Rp. 7,145,325.00 with B/C ratio of 1.13, whereas the value of NPV in 10% reduction of production costs was Rp. 5,957,814.00 with the B/C ratio of 1,12. The results of these research showed that the type rack of steamer oyster mushroom baglog was feasible.Keywords: mushroom steamer baglog, financial analysis, rack type steamer, oyster mushroom